2003
DOI: 10.1177/009318530303100105
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Courtroom Context on Children's Memory and Anxiety

Abstract: Modifications of the courtroom environment have been proposed to enhance the ability of child witnesses to offer complete and accurate testimony and reduce system-induced stress. However, these interventions have often been conceived without the benefit of empirical data demonstrating intervention efficacy. The present study examines the effects of the courtroom context on children's memory and anxiety. Eighty-one eight- to ten-year-olds participated in a staged event involving bodily touch, and two weeks late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 16 publications
0
44
0
Order By: Relevance
“…Nathanson and Saywitz 67 found, for example, that children provide more complete and accurate reports when questioned in a small private room than in a courtroom setting. Moreover, children had significantly more erratic heart rate patterns, indicative of a stress response, when interviewed in the courtroom.…”
Section: Discussionmentioning
confidence: 99%
“…Nathanson and Saywitz 67 found, for example, that children provide more complete and accurate reports when questioned in a small private room than in a courtroom setting. Moreover, children had significantly more erratic heart rate patterns, indicative of a stress response, when interviewed in the courtroom.…”
Section: Discussionmentioning
confidence: 99%
“…Quas, Wallin, Horwitz, Davis, and Lyon (2009) examined legal knowledge of 94 children aged 4-15 years and found that children who were more knowledgeable about the legal system were less distressed about attending their dependency court hearings. Nathanson and Saywitz (2003) examined the mock testimony of 81 8-to 10-year-olds in a courtroom at a university law school. They found that greater legal knowledge was linked to more detailed and accurate responses to questions about past events on the stand.…”
Section: Prepare Children With Age-appropriate Explanations Of the Pumentioning
confidence: 99%
“…while testifying in mock or actual trials), including when measured via physiological indices, is negatively related to children's ability to communicate and positively related to children's memory errors (e.g. Goodman, Taub, Jones, & England, 1992;Nathanson & Saywitz, 2003;Saywitz & Nathanson, 1993). Accordingly, it is important to distinguish the effects of arousal at encoding from arousal at retrieval when evaluating children's memory for emotional events.…”
mentioning
confidence: 99%